Constructions of cultural identities in newsreel cinema and television after 1945 (2018)
Studies on Chinese early cinema and its extended history in the Republican period (1911–1949) have trod a rocky path.1 After the founding of the People’s Republic in 1949, film historiography developed into a guarded field, even until today. In the immediate postwar time the term “Republican” was tainted by its attachment to the defeated Nationalist Party and its associated autocratic capitalism, corrupt bureaucracy, and dependence on foreign imperialist powers. Because of these negative associations, the notion of Republican cinema became suspect and was subject to monitoring and constraint, in the 1950s and after. The formerly “infamous” epoch was acknowledged as pivotal to the development of Chinese modernity when the censorious treatment of the Republican period relaxed in the twentyfirst century. Subsequently, Republican history was reconstructed by many scholars as Shanghai history, given the city’s unrivaled position (so-called Paris of the Orient) in early twentieth-century China. “Shanghai cinema” was then upheld as a synecdoche for cinema of the entire era as the city was then the country’s center of film production, distribution, and exhibition. The term “Shanghai,” despite its mythology (qipao, jazz, dance halls, intrigues, department stores, hippodrome, canidrome, dandies, motor cars, Ruan Lingyu, sultry Mandarin pop), risks reducing the scope of Republican history into a “looking glass” containing the most alluring facets. “Shanghai cinema,” too, when used as the overarching Republican cinema or Chinese cinema before 1949, entails a limited, partial approach to the vast terrains of cinema practices in many parts of China and colonies like Hong Kong, Taiwan, Macao, and the Chinese diaspora generally.